Educational attainment of children with neurodevelopmental conditions during primary school and timing of education support: a population cohort study using linked administrative data from Wales - Keating, Jennifer; O'Donovan, Lowri; Huxley, Katy; French, Rob (International Journal of Population Data Science, 2026)
Children with neurodevelopmental conditions may be at greater risk of lower attainment, however receiving education support (e.g. Special Education Needs (SEN) provision) may reduce the likelihood of poor outcomes. This study explored how the timing of educational support and neurodevelopmental diagnosis impacts primary school attainment. A cohort of 217,798 children born between 01/09/2002-31/08/2008 who were ever registered with a GP in Wales were identified. Using primary and secondary health records, we identified pupils with a recorded diagnosis of a neurodevelopmental condition. This was linked to administrative education data to explore the timing of SEN provision and attainment. At age 7, 38% of pupils with SEN and a neurodevelopmental diagnosis met attainment expectations, compared to 62% of those receiving SEN support without a clinical diagnosis and 84% of pupils not receiving any support. This increased to 48% by age 11, but was still below their peers. Approximately 25% and 23% of pupils with a neurodevelopmental diagnosis and no recorded SEN were not assessed at ages 7 and 11 respectively, in comparison to 14% and 13% of children without a clinical diagnosis at ages 7 and 11. Logistic regression models estimated whether timing of SEN identification and neurodevelopmental diagnosis were associated with achieving attainment expectations. Many children with a neurodevelopmental diagnosis or receiving SEN provision are not assessed or do not meet national attainment expectations by the end of primary school. Better monitoring and support for these children, perhaps through different assessment modes, are needed to allow them to fulfil their potential.